Study on immortalization of Mongolian sheep fibroblast cells - Bin. Liu; Shichao. Wang; Fanhua. Meng; Bei. Wu; Yanru Zhang; Junwei. Cao (Animal Biotechnology)
This study aims to establish an immortalized fibroblast cell line from Mongolian sheep. Primary Mongolian sheep fibroblasts (SSF) were isolated using tissue explant and enzymatic digestion methods, followed by microscopic observation, growth curve plotting, and karyotype analysis. The results confirmed the successful isolation of SSF. Human (hTERT) and sheep (sTERT) telomerase reverse transcriptase vectors were separately introduced into SSF, with cells passaged up to 36 generations following G418 selection. Microscopic examination and qRT-PCR results demonstrated that TERT transfection did not alter the morphology of SSF and led to stable, high levels of TERT expression (P < 0.01). Cell counting and flow cytometry revealed that TERT-transfected cells had higher viability and lower apoptosis rates compared to SSF (P < 0.05). Karyotype and soft agar colony formation assays indicated that hTERT and sTERT-transfected cells maintained normal characteristics without malignant transformation. β-galactosidase staining indicated that TERT transfection significantly reduced cellular senescence (P < 0.001). Additionally, sTERT-transfected cells exhibited higher TERT expression, enhanced viability, proliferation, and anti-senescence effects compared to hTERT-transfected cells (P < 0.05). In summary, the introduction of hTERT and sTERT effectively extends the lifespan of SSF, with sTERT demonstrating a more pronounced effect. This study provides critical evidence for preserving Mongolian sheep genetic resources and developing immortalized cell lines.